Determining the Position of Tip of Maxillary Canines in Relation to Commissure of Mouth and Midpupillary Line and its Correlation with Square, Ovoid and Tapering Arch Form - Mishra, Srijana; Mathema, S RB (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: Selection of appropriately sized maxillary denture teeth in various types of arch form is often a challenging aspect during complete denture rehabilitation. The correlation of facial anatomical landmarks may serve as a reliable predictor for the selection of teeth.Materials and methods: The maxillary arch impression of 113 dentate subjects were made, casts poured and divided into square, ovoid and tapering arch form. The position of tip of maxillary canines in relation to commissure of mouth and midpupillary line were determined by using vacuum formed template and pupillometer respectively.Results: The result showed the significant difference in mean distance from commissural to canine tip (p